Влияние фторида магния на светопропускание прозрачной керамики из алюмомагниевой шпинели - Хуан Ф.; Деулина Д. Е. Дарья Евгеньевна; Чэнь С.; Шевченко И. Н. Иван Николаевич; Пайгин В. Д. Владимир Денисович; Хасанов О. Л. Олег Леонидович (2024, 2024)
Заглавие с экрана